Purification and properties of an acid beta-xylosidase from Penicillium sclerotiorum - Knob, Adriana; Carmona, Eleonora Cano [UNESP] (Springer, 2012)
The beta-xylosidase from was purified to homogeneity by a rapid and inexpensive procedure involving ammonium sulphate fractionation and molecular exclusion chromatography. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis revealed two bands with an estimated molecular mass of 97 and 42 kDa, respectively. Electrophoretical homogeneity was observed under non-denaturing PAGE conditions. These results indicate that this protein has a dimeric structure. The molecular mass of the native enzyme estimated by molecular exclusion chromatography was 144 kDa. The enzyme is a glycoprotein with a 56.4% carbohydrate content. The pH and temperature optima were 2.5 and 60A degrees C, respectively. The enzyme remained stable over a pH range from 2.0 to 7.0 and at temperatures up to 60A degrees C for 375 min. All divalent cations tested, except for Hg2+, inhibited beta-xylosidase activity, especially at a concentration of10 mM. The purified enzyme was also sensitive to denaturing agents SDS and EDTA and was activated by thiol-containing reducing agents. The Michaelis-Menten constant for -nitrophenyl-beta--xylopyranoside was 0.78 mM, and the maximum reaction velocity was 0.51 mu mole of -nitrophenol min(-1) mg(-1) of protein. This is the first report on the purification and characterization of a beta-xylosidase from , which has potential applications in a number of biotechnological processes, such as animal feed, juice and wine industries.
Keywords: Penicillium sclerotiorum; beta-Xylosidase; Enzyme purification; Acid beta-xylosidase